Values of mutations of K-ras oncogene at codon 12 in detection of pancreatic cancer: 15-year experience - Mu, De-Qing (World J Gastroenterol, 2004)
AIM: To summarize progress in the study of K-ras gene studies in pancreatic cancer and its potential clinical significance in screening test for early detection of pancreatic cancer, and to differentiate pancreatic cancer from chronic pancreatitis in recent decade. METHODS: Literature search (MEDLINE 1986-2003) was performed using the key words K-ras gene, pancreatic cancer, chronic pancreatitis, and diagnosis. Two kind of opposite points of view on the significance of K-ras gene in detection early pancreatic cancer and differentiation pancreatic cancer from chronic pancreatitis were investigated. The presence of a K-ras gene mutation at codon 12 has been seen in 75% - 100% of pancreatic cancers, and is not rare in patients with chronic pancreatitis, and represents an increased risk of developing pancreatic cancer. However, the significance of the detection of this mutation in specimens obtained by needle aspiration from pure pancreatic juice and from stools for its utilization for the detection of early pancreatic cancer, and differentiation pancreatic cancer from chronic pancreatitis remains controversial. CONCLUSION: The value of K-ras gene mutation for the detection of early pancreatic cancer and differentiation pancreatic cancer from chronic pancreatitis remains uncertains in clinical pratice. Nevertheless, K-ras mutation screening may increase the sensitivity of FNA and ERP cytology and may be useful in identifying pancreatitis patients at high risk for developing cancer, and as a adjunct with cytology to differentiate pancreatic cancer from chronic pancreatitis.